Mister Exam

Other calculators

Integral of 13sin(3x)*e^(-3x) dx

Limits of integration:

from to
v

The graph:

from to

Piecewise:

The solution

You have entered [src]
  1                     
  /                     
 |                      
 |               -3*x   
 |  13*sin(3*x)*E     dx
 |                      
/                       
0                       
01e3x13sin(3x)dx\int\limits_{0}^{1} e^{- 3 x} 13 \sin{\left(3 x \right)}\, dx
Integral((13*sin(3*x))*E^(-3*x), (x, 0, 1))
Detail solution
  1. There are multiple ways to do this integral.

    Method #1

    1. Let u=3xu = 3 x.

      Then let du=3dxdu = 3 dx and substitute 13du3\frac{13 du}{3}:

      13eusin(u)3du\int \frac{13 e^{- u} \sin{\left(u \right)}}{3}\, du

      1. The integral of a constant times a function is the constant times the integral of the function:

        eusin(u)du=13eusin(u)du3\int e^{- u} \sin{\left(u \right)}\, du = \frac{13 \int e^{- u} \sin{\left(u \right)}\, du}{3}

        1. Let u=uu = - u.

          Then let du=dudu = - du and substitute dudu:

          eusin(u)du\int e^{u} \sin{\left(u \right)}\, du

          1. Use integration by parts, noting that the integrand eventually repeats itself.

            1. For the integrand eusin(u)e^{u} \sin{\left(u \right)}:

              Let u(u)=sin(u)u{\left(u \right)} = \sin{\left(u \right)} and let dv(u)=eu\operatorname{dv}{\left(u \right)} = e^{u}.

              Then eusin(u)du=eusin(u)eucos(u)du\int e^{u} \sin{\left(u \right)}\, du = e^{u} \sin{\left(u \right)} - \int e^{u} \cos{\left(u \right)}\, du.

            2. For the integrand eucos(u)e^{u} \cos{\left(u \right)}:

              Let u(u)=cos(u)u{\left(u \right)} = \cos{\left(u \right)} and let dv(u)=eu\operatorname{dv}{\left(u \right)} = e^{u}.

              Then eusin(u)du=eusin(u)eucos(u)+(eusin(u))du\int e^{u} \sin{\left(u \right)}\, du = e^{u} \sin{\left(u \right)} - e^{u} \cos{\left(u \right)} + \int \left(- e^{u} \sin{\left(u \right)}\right)\, du.

            3. Notice that the integrand has repeated itself, so move it to one side:

              2eusin(u)du=eusin(u)eucos(u)2 \int e^{u} \sin{\left(u \right)}\, du = e^{u} \sin{\left(u \right)} - e^{u} \cos{\left(u \right)}

              Therefore,

              eusin(u)du=eusin(u)2eucos(u)2\int e^{u} \sin{\left(u \right)}\, du = \frac{e^{u} \sin{\left(u \right)}}{2} - \frac{e^{u} \cos{\left(u \right)}}{2}

          Now substitute uu back in:

          eusin(u)2eucos(u)2- \frac{e^{- u} \sin{\left(u \right)}}{2} - \frac{e^{- u} \cos{\left(u \right)}}{2}

        So, the result is: 13eusin(u)613eucos(u)6- \frac{13 e^{- u} \sin{\left(u \right)}}{6} - \frac{13 e^{- u} \cos{\left(u \right)}}{6}

      Now substitute uu back in:

      13e3xsin(3x)613e3xcos(3x)6- \frac{13 e^{- 3 x} \sin{\left(3 x \right)}}{6} - \frac{13 e^{- 3 x} \cos{\left(3 x \right)}}{6}

    Method #2

    1. Let u=3xu = - 3 x.

      Then let du=3dxdu = - 3 dx and substitute 13du3\frac{13 du}{3}:

      13eusin(u)3du\int \frac{13 e^{u} \sin{\left(u \right)}}{3}\, du

      1. The integral of a constant times a function is the constant times the integral of the function:

        eusin(u)du=13eusin(u)du3\int e^{u} \sin{\left(u \right)}\, du = \frac{13 \int e^{u} \sin{\left(u \right)}\, du}{3}

        1. Use integration by parts, noting that the integrand eventually repeats itself.

          1. For the integrand eusin(u)e^{u} \sin{\left(u \right)}:

            Let u(u)=sin(u)u{\left(u \right)} = \sin{\left(u \right)} and let dv(u)=eu\operatorname{dv}{\left(u \right)} = e^{u}.

            Then eusin(u)du=eusin(u)eucos(u)du\int e^{u} \sin{\left(u \right)}\, du = e^{u} \sin{\left(u \right)} - \int e^{u} \cos{\left(u \right)}\, du.

          2. For the integrand eucos(u)e^{u} \cos{\left(u \right)}:

            Let u(u)=cos(u)u{\left(u \right)} = \cos{\left(u \right)} and let dv(u)=eu\operatorname{dv}{\left(u \right)} = e^{u}.

            Then eusin(u)du=eusin(u)eucos(u)+(eusin(u))du\int e^{u} \sin{\left(u \right)}\, du = e^{u} \sin{\left(u \right)} - e^{u} \cos{\left(u \right)} + \int \left(- e^{u} \sin{\left(u \right)}\right)\, du.

          3. Notice that the integrand has repeated itself, so move it to one side:

            2eusin(u)du=eusin(u)eucos(u)2 \int e^{u} \sin{\left(u \right)}\, du = e^{u} \sin{\left(u \right)} - e^{u} \cos{\left(u \right)}

            Therefore,

            eusin(u)du=eusin(u)2eucos(u)2\int e^{u} \sin{\left(u \right)}\, du = \frac{e^{u} \sin{\left(u \right)}}{2} - \frac{e^{u} \cos{\left(u \right)}}{2}

        So, the result is: 13eusin(u)613eucos(u)6\frac{13 e^{u} \sin{\left(u \right)}}{6} - \frac{13 e^{u} \cos{\left(u \right)}}{6}

      Now substitute uu back in:

      13e3xsin(3x)613e3xcos(3x)6- \frac{13 e^{- 3 x} \sin{\left(3 x \right)}}{6} - \frac{13 e^{- 3 x} \cos{\left(3 x \right)}}{6}

  2. Now simplify:

    132e3xsin(3x+π4)6- \frac{13 \sqrt{2} e^{- 3 x} \sin{\left(3 x + \frac{\pi}{4} \right)}}{6}

  3. Add the constant of integration:

    132e3xsin(3x+π4)6+constant- \frac{13 \sqrt{2} e^{- 3 x} \sin{\left(3 x + \frac{\pi}{4} \right)}}{6}+ \mathrm{constant}


The answer is:

132e3xsin(3x+π4)6+constant- \frac{13 \sqrt{2} e^{- 3 x} \sin{\left(3 x + \frac{\pi}{4} \right)}}{6}+ \mathrm{constant}

The answer (Indefinite) [src]
  /                                                                
 |                                         -3*x       -3*x         
 |              -3*x          13*cos(3*x)*e       13*e    *sin(3*x)
 | 13*sin(3*x)*E     dx = C - ----------------- - -----------------
 |                                    6                   6        
/                                                                  
e3x13sin(3x)dx=C13e3xsin(3x)613e3xcos(3x)6\int e^{- 3 x} 13 \sin{\left(3 x \right)}\, dx = C - \frac{13 e^{- 3 x} \sin{\left(3 x \right)}}{6} - \frac{13 e^{- 3 x} \cos{\left(3 x \right)}}{6}
The graph
0.001.000.100.200.300.400.500.600.700.800.905-5
The answer [src]
                -3       -3       
13   13*cos(3)*e     13*e  *sin(3)
-- - ------------- - -------------
6          6               6      
13sin(3)6e313cos(3)6e3+136- \frac{13 \sin{\left(3 \right)}}{6 e^{3}} - \frac{13 \cos{\left(3 \right)}}{6 e^{3}} + \frac{13}{6}
=
=
                -3       -3       
13   13*cos(3)*e     13*e  *sin(3)
-- - ------------- - -------------
6          6               6      
13sin(3)6e313cos(3)6e3+136- \frac{13 \sin{\left(3 \right)}}{6 e^{3}} - \frac{13 \cos{\left(3 \right)}}{6 e^{3}} + \frac{13}{6}
13/6 - 13*cos(3)*exp(-3)/6 - 13*exp(-3)*sin(3)/6
Numerical answer [src]
2.25823622401557
2.25823622401557

    Use the examples entering the upper and lower limits of integration.